Variability for Seed Reserve Traits and Their Interrelationship among Hybrids and Varieties of Cotton - SANTHY V; DEBASHISH PAUL; PRATIK DHAKADE; BHUMESH FANDEY (Seed Research, 2026)
Investigation was carried out to examine the influence of seed weight and seed reserve factors on the development of superior seedling mass in cotton. The objectives included study on variability with respect to seed reserve utilization traits such as initial seed weight, seed reserve content and seed reserve depletion, seed reserve depletion rate, seed reserve respiration and seed reserve utilization efficiency as well as their interrelationships in cotton. The genotypes included seeds of hybrids, varieties of hirsutum species and arboreum species which varied widely in their initial seed weight. The comparison of traits among genotypes showed initial seed weight, seedling dry weight and seed reserve content significantly higher for hybrids followed by G. hirsutum and G. arboreum varieties respectively. However, the Seed Reserve Utilization Efficiency (SRUE) showed no variation irrespective of the seeds being hybrids or varieties. Correlation study revealed seed weight having significant positive correlation with seed reserve content measured as seed reserve depletion in seeds of all genotypes. However, the conversion efficiency of seed reserve into seedling tissue (SRUE) showed negative correlation with all the studied traits viz. initial seed weight, seed reserve content and seed reserve depletion rate and, was the same across species or type of seeds. This indicated that higher seed weight or higher seed reserve in the seed are not the only factors responsible for superior seedling emergence and growth. These findings could be of use for development of improved germplasm with a high conversion rate of seed storage reserves.